Bilateral Transcranial Magnetic Stimulation of the Prefrontal Cortex Reduces Cocaine Intake: A Pilot Study - Bolloni, Corinna; Panella, Riccardo; Pedetti, Mariano; Frascella, Anna Grazia; Gambelunghe, Cristiana; Piccoli, Tommaso; Maniaci, Giuseppe; Brancato, Anna; Cannizzaro, Carla; Diana, Marco (Frontiers in Psychiatry, 2016)
Background: Chronic cocaine consumption is associated to a decrease in mesolimbic dopamine transmission that maintains drug intake. Transcranial Magnetic Stimulation (TMS) is gaining reliability a useful therapeutic tool in drug addiction since it can modulate cortico-limbic activity resulting in reduction of drug craving. Aims: In the present study we investigated the therapeutic effect of bilateral TMS of prefrontal cortex (PFC) in reducing cocaine intake, in a sample of treatment-seeking patients with current cocaine use disorder (DSM-V). Methods: 10 cocaine addicts (DSM-V) were randomly assigned to the active or sham stimulation protocol in a double-blind experimental design. Twelve repetitive TMS (rTMS) sessions were administered 3 times a week for 4 weeks at 100% of motor threshold, over bilateral PFC. Cocaine intake (ng/mg) was assessed by hair analysis at baseline (before treatment, T0), after one month (end of treatment, T1), 3 (T2) and 6 (T3) months later. All subjects received psychological support weekly. Results: The two-way ANOVA for repeated measures did not show a significant effect of the interaction between time and treatment (F4,32= 0.35; p=.87). Despite that result indicated no difference in the effect of the two conditions (active vs sham) along time, a decreasing trend in cocaine consumption in active TMS group (F3,23=3.42; p=.04) vs sham (F3,15=1.88; p=.20) was observed when we performed exploratory analysis with time as factor . Indeed, Post-hoc comparisons showed a significant reduction in the amount of cocaine detected from the onset to three months later (T0-T2; p=.02) and to the end of treatment (T0-T3; p=.01) in addicts from the active group. Conclusions: Bilateral rTMS of PFC at 10 Hz did not show a significant effect on cocaine intake compared to sham. However, a long-term reduction in cocaine intake in active TMS treated patients was observed when we considered the time as factor. Further studies are required to confirm these encouraging but preliminary findings, in order to consolidate rTMS as a valid tool to treat cocaine addiction.